The Perception of Fifth Semester Students in Learning Listening Strategies at Widya Gama Mahakam Samarinda University in Academic Year 2016/2017 - Maimunah Rani Fitri (Script Journal: Journal of Linguistics and English Teaching, 2016)
The listening skills is viewed as an important skill to master, because from listening we can understand what are people saying, we can get the meaning of every words that speaker talk about, and it is important in process of listening comprehension. The Objective of this research is to find out the perception of fifth semester students of Widya Gama Mahakam Samarinda University in learning listening comprehension. In this research the main theories from Gay (2006) and from (Howitt & Cramer, 2009). The researcher uses Descriptive Quantitative research. The subject of this study was the fifth semester students of English Department at Widya Gama Mahakam Samarinda University. The researcher uses a questionnaire as an instrument to collect the data, and then representing the data in analysis and concluding the result of analysis. The result of questionnaire showed that students perception toward the strategies in learning listening were 12 students or 171% very often used Social strategies, 15 students or 171% often used Affective and Compensation strategies.